The Impact of Rotavirus Vaccines on Genotype Diversity: A Comprehensive Analysis of 2 Decades of Australian Surveillance Data. (22nd May 2018) - Roczo-Farkas, Susie; Kirkwood, Carl D; Cowley, Daniel; Barnes, Graeme L; Bishop, Ruth F; Bogdanovic-Sakran, Nada; Boniface, Karen; Donato, Celeste M; Bines, Julie E
Abstract : This study describes circulating rotavirus genotypes before and after rotavirus vaccine introduction into the Australian national immunization program. Increased genotype diversity was observed after vaccine introduction, and different genotypes sustained dominance according to vaccine use, suggesting vaccine-related selective pressure. Abstract: Background: Introduction of rotavirus vaccines into national immunization programs (NIPs) could result in strain selection due to vaccine-induced selective pressure. This study describes the distribution and diversity of rotavirus genotypes before and after rotavirus vaccine introduction into the Australian NIP. State-based vaccine selection facilitated a unique comparison of diversity in RotaTeq and Rotarix vaccine states. Methods: From 1995 to 2015, the Australian Rotavirus Surveillance Program conducted genotypic analysis on 13051 rotavirus-positive samples from children <5 years of age, hospitalized with acute gastroenteritis. Rotavirus G and P genotypes were determined using serological and heminested multiplex reverse-transcription polymerase chain reaction assays. Results: G1P[8] was the dominant genotype nationally in the prevaccine era (1995–2006). Following vaccine introduction (2007–2015), greater genotype diversity was observed with fluctuating genotype dominance. Genotype distribution varied based on the vaccine implemented, with G12P[8] dominant in states using RotaTeq, and equine-like G3P[8] and G2P[4] dominant in states and territories using Rotarix. Conclusions: The increased diversity and differences in genotype dominance observed in states using RotaTeq (G12P[8]), and in states and territories using Rotarix (equine-like G3P[8] and G2P[4]), suggest that these vaccines exert different immunological pressures that influence the diversity of rotavirus strains circulating in Australia.